2011
DOI: 10.1175/2010jas3460.1
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Rossby Wave Breaking on the Southern Hemisphere Tropopause

Abstract: A 30-yr climatology of Rossby wave breaking (RWB) on the Southern Hemisphere (SH) tropopause is formed using 30 yr of reanalyses. Composite analysis of potential vorticity and meridional fluxes of wave activity show that RWB in the SH can be divided into two broad categories: anticyclonic and cyclonic events. While there is only weak asymmetry in the meridional direction and most events cannot be classified as equatorward or poleward in terms of the potential vorticity structure, the position and structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 45 publications
8
45
1
Order By: Relevance
“…The equatorward displacement of strong TT frequency at the eastern boundaries of the North Pacific and North Atlantic basins is consistent with enhanced RWB at the exits of the midlatitude 330-K waveguides as shown by Martius et al (2008). The strong TT frequency is more zonally uniform in the Southern Hemisphere although the presence of the polar front jet south of the South Atlantic basin and south Indian Basin reduces Rossby wave activity in the region, particularly in the early summer season (Ndarana and Waugh 2011). By the late summer, wave breaking on the 330-K isentropic surface occurs across most of the southern oceans, leading to a zonal expansion of the high-frequency (.75%) strong TT region as shown in Fig.…”
Section: Pathway Climatologysupporting
confidence: 71%
See 3 more Smart Citations
“…The equatorward displacement of strong TT frequency at the eastern boundaries of the North Pacific and North Atlantic basins is consistent with enhanced RWB at the exits of the midlatitude 330-K waveguides as shown by Martius et al (2008). The strong TT frequency is more zonally uniform in the Southern Hemisphere although the presence of the polar front jet south of the South Atlantic basin and south Indian Basin reduces Rossby wave activity in the region, particularly in the early summer season (Ndarana and Waugh 2011). By the late summer, wave breaking on the 330-K isentropic surface occurs across most of the southern oceans, leading to a zonal expansion of the high-frequency (.75%) strong TT region as shown in Fig.…”
Section: Pathway Climatologysupporting
confidence: 71%
“…In the Southern Hemisphere, a single peak in troughinduced frequency is evident near the equator in the central South Pacific. These regions lie equatorward and westward of the primary subtropical RWB centers (Postel and Hitchman 1999;Ndarana and Waugh 2011), identifiable in Fig. 4 as areas in which the separation between the plotted isentropes increases.…”
Section: Pathway Climatologymentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown that wave breaking in the troposphere and in the tropopause regions depends on the wave number (Orlanski, 2003;Riviere and Orlanski, 2007), and on the zonal variation of the zonal flow along jets Waugh, 1996, 2003;Swanson et al, 1997;Swanson, 2000;Ndarana and Waugh, 2011;Esler and Haynes, 1999). It was suggested that wave breaking tends to occur in regions where the mean zonal wind is weak.…”
Section: Introductionmentioning
confidence: 99%